Pea Aphid Survival Assays on Arabidopsis thaliana - David Prince; Sam Mugford; Thomas Vincent; Saskia Hogenhout (Bio-Protocol, 2014)
Aphids are phloem-feeding insects that successfully colonize specific host plant species. Aphid performance on a given plant is commonly measured by assessing fecundity of an aphid species that is adapted to the host. However, this approach may not reveal roles for plant genes in defense pathways that adapted aphids suppress. The host range of the pea aphid (Acyrthosiphon pisum) is mostly restricted to plants of the legume family, and does not include Arabidopsis (Arabidopsis thaliana). Pea aphids die within a few days of being placed on Arabidopsis plants, and their survival therefore provides a sensitive measure of the status of the host plant defenses. This protocol describes how to measure the survival rate of the pea aphid on the non-host plant Arabidopsis. The protocol consists of two phases: first, obtaining a population of pea aphids of synchronized age; and secondly measuring their survival on Arabidopsis plants.